Portrait of a Labour Spy: The Case of Robert Raglan Gosden, 1882-1961 - Leier, Mark (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1998)
Portrait of a Labour Spy: The Case ofRobert Raglan Gosden, 1882-1961 Mark Leier This paper examines the life of Robert Raglan Gosden, 1882-1961. Gosden was an unskilled worker who joined the Industrial Workers of the World and advocated violent revolution. He took part in the Vancouver Island mining strikes of 1912-1914, and was a key player in the 1916 provincial election scandal. By 1919, however, he was an informant for the RCMP. The paper outlines Gosden's career and analyzes the complex way his class experience shaped his construction of masculinity as well as his radical politics and his later activity as a labour spy.